Looking back at al-Andalus : the poetics of loss and nostalgia in medieval Arabic and Hebrew literature - Elinson, Alexander E. (Brill Studies in Middle Eastern Literatures, 2009)
Looking Back at al-Andalus focuses on Arabic and Hebrew Literature that expresses the loss of al-Andalus from multiple vantage points. In doing so, this book examines the definition of al-Andalus' literary borders, the reconstruction of which navigates between traditional generic formulations and actual political, military and cultural challenges. By looking at a variety of genres, the book shows that literature aiming to recall and define al-Andalus expresses a series of symbolic literary objects more than a geographic and political entity fixed in a single time and place. Looking Back at al-Andalus offers a unique examination into the role of memory, language, and subjectivity in presenting a series of interpretations of what al-Andalus represented to different writers at different historical-cultural moments.